Characterization of the response of primary cells relevant to dialysis-related amyloidosis to β2-microglobulin monomer and fibrils. - Morwenna Y Porter (Public Library of Science (PLoS), 2011)
The formation of insoluble amyloid fibrils is associated with an array of devastating human diseases. Dialysis-related amyloidosis (DRA) is a severe complication of hemodialysis that results in the progressive destruction of the bones and joints. Elevated concentrations of β(2)-microglobulin (β(2)m) in the serum of subjects on hemodialysis promote the formation of amyloid fibrils in the osteoarticular tissues, but the cellular basis for the destruction of these tissues in DRA is poorly understood. In this study we performed a systematic analysis of the interaction of monomeric and fibrillar β(2)m with primary human cells of the types present in the synovial joints of subjects with DRA. Building upon observations that macrophages infiltrate β(2)m amyloid deposits in vivo we demonstrate that monocytes, the precursors of macrophages, cannot degrade β(2)m fibrils, and that both monomeric β(2)m and fibrillar β(2)m are cytotoxic to these cells. β(2)m fibrils also impair the formation of bone resorbing osteoclasts from monocytes and reduce the viability of osteoblasts, the cell type that produces bone. As a consequence, we predict that β(2)m amyloid will disrupt the remodelling of the bone, which is critical for the maintenance of this tissue. Moreover, we show that β(2)m fibrils reduce the viability of chondrocytes, rationalizing the loss of cartilage in DRA. Together, our observations demonstrate that β(2)m cytotoxicity has multiple cellular targets in the osteoarticular tissues and is likely to be a key factor in the bone and joint destruction characteristic of DRA.